Grounding Surah Al-Fatihah as a Foundational Framework for Transforming Binary Thought toward Progressive, National, and Cultural Islam through a Time-Based Fourier Series Approach - Bambang Judi Bagiono; Warno Warno; Hendarto D Hendarto D; Bambang Subana Afandi; M. Firdaus (PT. Student Rihlah Indonesia, 2026)
This article aims to position Surah Al-Fatihah as a foundational epistemological framework for transforming binary thinking toward Progressive, National, and Cultural Islam. Methodologically, this study adopts an interdisciplinary qualitative approach that integrates thematic Qur’anic interpretation, philosophy of knowledge, and a conceptual analogy derived from time-based Fourier series. The findings suggest that a time-based Fourier approach enables a paradigmatic shift from rigid binary logic toward an integrative spectral model of Islamic thought. This transformation supports the development of Progressive Islam that engages constructively with science and modernity, National Islam that harmonizes religious values with constitutional frameworks, and Cultural Islam that embraces local wisdom as an authentic expression of universal Islamic principles. Consequently, Surah Al-Fatihah emerges as an epistemic, ethical, and civilizational foundation for an inclusive, contextual, and future-oriented Islamic worldview.